2014
DOI: 10.1038/srep05087
|View full text |Cite
|
Sign up to set email alerts
|

Ag-SiO2-Er2O3 Nanocomposites: Highly Effective Upconversion Luminescence at High Power Excitation and High Temperature

Abstract: Rare Earth (RE) activated upconversion phosphors (UCPs), have demonstrated significant application potentials in some front fields, including solar energy conversion and bio-application. However, some bottleneck problems should be overcame, such as the lower upconversion efficiency, narrower excitation band, concentration-quenching and temperature-quenching. To solve these problems, the Ag-SiO2-Er2O3 nanocomposites were fabricated, in which the upconversion luminescence (UCL) of Er2O3 was white broadband. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 39 publications
4
25
0
1
Order By: Relevance
“…This trend is also observed in other literatures [22][23] , which is probably caused by photon avalanche or thermal avalanche 24 . Fig.…”
Section: Photon Energy Upconversion Under Nir Excitationsupporting
confidence: 80%
See 1 more Smart Citation
“…This trend is also observed in other literatures [22][23] , which is probably caused by photon avalanche or thermal avalanche 24 . Fig.…”
Section: Photon Energy Upconversion Under Nir Excitationsupporting
confidence: 80%
“…On the other hand, at high pumping densities, the 3d levels of Cu 2+ would become saturated, therefore enabling the promotion of electrons further to the conduction band. This multiphoton process associate with a photon avalanche mechanism was supported by the photocurrent measurement for several RE 3+ doped compounds and the white emission has been ascribed to a charge transfer process 22,[33][34][35] . Indeed, laser damage occurs for the copper silicate pigments, despite that thermal analysis indicate the stability of these compounds under 1273 K (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies showed that most core-sheath fluorescent materials were designed with Ag as the core and a luminescent substrate as the sheath [16,28,29,31]. In the present study, coresheath nanofibers with Ag-NPs/PVP as the core and Tb(acac) 3 phen/PLLA as the sheath were also prepared to further verify the effect of the location of Ag layer in the core-sheath structure on the fluorescence intensity of the fibers.…”
Section: Resultsmentioning
confidence: 94%
“…In previous research, the methods adopted to control the distance between the metal nanoparticles and the RE complexes include (1) the import of long-chain macromolecules, biomacromolecules, or multilayer Langmuir-Blodgett (LB) films to metal nanoparticles [24][25][26][27], a relatively complex and difficult process because of the complicated physical and chemical reactions involved; (2) the introduction of an inorganic silica (SiO 2 ) transition layer, the thickness of which can be controlled by reaction time and temperature [28][29][30][31]. However, in most previous studies, a precious metal was used as the inner layer and a fluorophore was used as the outer layer.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, numerous works have reported a broadband, white-light emission from insulating powders under intense, near infrared (IR) excitation. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The materials investigated are usually nano-powders of insulators, such as yttrium oxide, yttrium silicate, Al 2 O 3 , GGG, and others, either pure or doped with rare earth ions (e.g. Er, Nd, Yb, Tm) or transition metal ions (e.g.…”
mentioning
confidence: 99%